2003
DOI: 10.4219/jsge-2003-430
|View full text |Cite
|
Sign up to set email alerts
|

Talent Search: Student and Parent Perceptions of Out-of-Level Testing

Abstract: Every year, hundreds of thousands of academically gifted 7th- and 8th-grade students participate in 1 of 4 regional or several local talent searches, through which they take the ACT or SAT as an out-of-level test. Participation in a talent search offers young students the opportunity to learn about their abilities, practice taking the standardized test they will eventually take for college admittance, obtain information about educational opportunities, and become eligible for rigorous summer and weekend educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Four studies of nontraditional programming examined the views of parents whose gifted children participated in programs outside public education in specialized schools (Hishinuma, 2000), early entrance programs (Noble, Childers, & Vaughan, 2008), talent search programs (Jarosewich & Stocking, 2003), and homeschool settings (Hopper, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies of nontraditional programming examined the views of parents whose gifted children participated in programs outside public education in specialized schools (Hishinuma, 2000), early entrance programs (Noble, Childers, & Vaughan, 2008), talent search programs (Jarosewich & Stocking, 2003), and homeschool settings (Hopper, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Specific themes these authors identified included families’ roles in providing enriched language and learning experiences and the potential roles of affective differences in areas such as family environment, sibling issues, emotional development, and growing up. Other recent research that captures parents’ understanding and perceptions of giftedness can be characterized as including concerns within specific cultures, parents’ perceptions of giftedness and ability, their attitudes toward gifted programming, and views on nontraditional services (see, for example, Campbell & Mandel, 1990; Jarosewich & Stocking, 2003; Shumow, 1997; Strom, Johnson, & Strom, 1990). This literature also hints at the perceived slights and actual inadequacies that parents may encounter when engaging with schools about the education of their children (see, for example, F.…”
Section: Introductionmentioning
confidence: 99%
“…Participation in talent search testing enhanced students' knowledge about the nature of their academic abilities (Ablard, Mills, & Hoffhines, 1996;Assouline & Lupkowski-Shoplik, 1997;Brody, 1998;Jarosewich & Stocking, 2003;VanTassel-Baska, 1989) and educational and career aspirations (Benbow & Arjmand, 1990;Brody;Burton, 1988;Wilder & Casserly, 1988; VanTassel-Baska). Talent search educational R e e programs provided students with opportunities to experience greater academic challenge (Enersen, 1993;Mills, Ablard, & Lynch, 1992), to take more rigorous advanced courses including AP and honors levels (Barnett & Durden, 1993), to have greater acceleration during high school (Barnett & Durden;OlszewskiKubilius & Grant, 1996), and to increase their educational aspirations (OlszewskiKubilius & Grant).…”
Section: Identifying Gifted Students Via Talent Searchmentioning
confidence: 95%
“…A large body of research about talent search testing and its educational programs has accumulated (e.g., Ablard, Mills, & Hoffhines, 1996;Assouline & Lupkowski-Shoplik, 1997;Barnett & Durden, 1993;Bartkovich & Mezynski, 1981;Benbow, 1992aBenbow, , 1992bBenbow & Arjmand, 1990;Benbow, Perkins, & Stanley, 1983;Brody, 1998;Burton, 1988;Enersen, 1993;Jarosewich & Stocking, 2003;Kolitch & Brody, 1992;Lee, Matthews, & Olszewski-Kubilius, in press;Lynch, 1992;Mills, Ablard, & Lynch, 1992;Olszewski-Kubilius, 1998a, 1998bOlszewski-Kubilius & Grant, 1996;Olszewski-Kubilius & Lee, 2005;Swiatek & Benbow, 1991;Swiatek & Lupkowski-Shoplik, in press;VanTassel-Baska, 1998;Wilder & Casserly, 1988). Talent search was developed by Dr. Julian Stanley at Johns Hopkins University as part of the Study of Mathematically Precocious Youth (SMPY) in the early 1970s.…”
Section: Identifying Gifted Students Via Talent Searchmentioning
confidence: 98%
“…Many studies use academic achievement to define giftedness (Hoover & Feldhusen, 1990;Shore, 2000), others use various cut-off scores on tests such as the IQ test (Hollingworth, 1942;Gottfried et al, 1994) and the Scholastic Aptitude Test (SAT) (Stanley et. al., 1974;Jarosewich & Stocking, 2003). Still others rely on social criteria, such as teacher nominations (Kammer, 1984; for a review, see Konstantopoulous et al, 2001).…”
Section: Prodigies and Gifted Studentsmentioning
confidence: 99%